2018
DOI: 10.1002/mc.22950
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circRNA_0006528 as a competing endogenous RNA promotes human breast cancer progression by sponging miR‐7‐5p and activating the MAPK/ERK signaling pathway

Abstract: Emerging research has indicated that circular RNAs (circRNAs), a novel class of noncoding RNAs, play a vital role in human tumorigenesis and progression. Our previous results suggested that hsa_circ_0006528 (circ_0006528), a circRNA with an unknown function, mediates adriamycin resistance in human breast cancer cells. However, the role of circ_0006528 in breast cancer progression remains unknown. Here, we investigated the probable involvement of circ_0006528 in breast cancer. We analyzed a cohort of 97 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 42 publications
2
72
0
Order By: Relevance
“…Recent studies have highlighted promising potential of circRNAs as important modulators in human cancers 17,18. Similar with our findings, a recent study linked the high expression of hsa_ circRNA_0006528 to advanced tumour-node-metastasis stage and poor outcomes in breast cancer, while inhibition of this circRNA delayed cancer development 19. Similar with our findings, a recent study linked the high expression of hsa_ circRNA_0006528 to advanced tumour-node-metastasis stage and poor outcomes in breast cancer, while inhibition of this circRNA delayed cancer development 19.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Recent studies have highlighted promising potential of circRNAs as important modulators in human cancers 17,18. Similar with our findings, a recent study linked the high expression of hsa_ circRNA_0006528 to advanced tumour-node-metastasis stage and poor outcomes in breast cancer, while inhibition of this circRNA delayed cancer development 19. Similar with our findings, a recent study linked the high expression of hsa_ circRNA_0006528 to advanced tumour-node-metastasis stage and poor outcomes in breast cancer, while inhibition of this circRNA delayed cancer development 19.…”
supporting
confidence: 90%
“…Similar with our findings, a recent study linked the high expression of hsa_ circRNA_0006528 to advanced tumour-node-metastasis stage and poor outcomes in breast cancer, while inhibition of this circRNA delayed cancer development. 19 Analogously, up-regulation of hsa_cir-cRNA_0072995 is determined in breast cancer cells; in contrast, the silencing of hsa_circRNA_0072995 restrained aggressive malignant behaviours in breast cancer. 20 Moreover, hsa_circRNA_002178 silencing inhibited inflammation in vivo through reducing TNF-α and IL-6 levels and prevented tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study reflected myricetin exerted its efficacy via JAK1/STAT3 and MEK/ERK in skin carcinoma (Kang, Jung, Lee, & Lee, 2011). Other studies pointed out circ0009910 enhanced carcinoma via the JAK1/STAT3 pathway (Deng et al, 2018) and circRNA0006528 enhanced breast carcinoma via the MEK/ERK pathway (Gao et al, 2019). Moreover, research pointed out miR-23a exerted efficacies in pancreatic carcinoma via JAK/STAT pathway and miR-520c exerted efficacies in fibrosarcoma via MEK/ERK signaling pathway (Liu & Wilson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that circRNA participates in the regulation of tumor cell progression in a variety of malignancies, including aspects such as proliferation, metastasis, apoptosis, and epithelial-mesenchymal transition. 28,29 For instance, circ_0006528 facilitates human breast cancer progression by activating the MAPK/ERK signaling pathway 30 ; circ_ 0058124 modulates the carcinogenesis and invasion of NOTCH3/GATAD2A papillary thyroid carcinoma with high expression linked to adverse pathological parameters in patients, 31 and circ-PRKCI enhances the proliferation and invasion of ESCC via upregulating AKT3 expression. 32 In this study, we demonstrated that compared with normal tissues, circ_0000654 expression in ESCC tissues was remarkably increased, and its high expression was linked to the higher T stage and lymph node metastasis of ESCC patients.…”
Section: Discussionmentioning
confidence: 99%